2007
DOI: 10.1097/qad.0b013e32823ecf5b
|View full text |Cite
|
Sign up to set email alerts
|

Changing patterns of clinical events in perinatally HIV-1-infected children during the era of HAART

Abstract: Progressive reductions of both mortality and rates of class B and C clinical events, including organ complications, were evidenced in the HAART era. Nevertheless, severe bacterial infections, particularly pneumonia, still occurred at considerable high rates, even in the absence of a severe CD4 cell depletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 19 publications
7
51
3
1
Order By: Relevance
“…However we identified a persisting relative importance of some specific events such as invasive bacterial diseases. A study conducted in Italy in a cohort of 1,402 children exposed to HIV through MTCT and representative of the pre-HAART (1985-1995) and HAART (1996-2000 and 2001-2005) periods showed the progressive reduction in the rate of specific clinical events, similar to our study with persisting high rates of serious bacterial infections, particularly pneumonia [11]. In Brazil, a previous study conducted in Minas Gerais State (Southeast region) in a referral center showed that the effectiveness of HAART was associated with significant reduction in the incidence of opportunistic infections in 371 children observed between 1989 and 2003 [18].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…However we identified a persisting relative importance of some specific events such as invasive bacterial diseases. A study conducted in Italy in a cohort of 1,402 children exposed to HIV through MTCT and representative of the pre-HAART (1985-1995) and HAART (1996-2000 and 2001-2005) periods showed the progressive reduction in the rate of specific clinical events, similar to our study with persisting high rates of serious bacterial infections, particularly pneumonia [11]. In Brazil, a previous study conducted in Minas Gerais State (Southeast region) in a referral center showed that the effectiveness of HAART was associated with significant reduction in the incidence of opportunistic infections in 371 children observed between 1989 and 2003 [18].…”
Section: Discussionsupporting
confidence: 86%
“…In our study cryptosporidiosis was significantly reduced (more than five times), as observed in other studies [11,29]. For other diseases (excluding cryptococcosis), despite the indication of reduction in the proportion of cases in the second period, there was not a significant difference between the periods.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Introduction of antiretroviral treatment ( ART) has decreased mortality and progression to advanced human immunodeficiency virus (AIDS) in perinatally HIV-infected children, but information on modification of the rate of specific clinical events is limited [4] . Understanding the epidemiology of paediatric HIV infection and progression of disease may reveal opportunities to reduce and perhaps eliminate perinatal transmission in resource poor settings; and when prevention is not possible, identification of infected children will allow appropriate treatment to significantly improve their quality of life.…”
Section: Introductionmentioning
confidence: 99%